PENGARUH MOTIVASI DAN BUDAYA KERJA TERHADAP KINERJA KARYAWAN RUMAH SAKIT DJATIROTO DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Kurniahadi, Didik; Fandiyanto, Randika; Anshory, Muhammad Iqbal (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
This research aims to examine the influence of (1) motivation on job satisfaction, (2) work culture on job satisfaction, (3) motivation on performance, (4) culture on performance, and (5) job satisfaction on performance. The design of this research is causal quantitative research. The research subjects were employees of Djatiroto Hospital, Lumajang Regency and the objects were motivation, work culture, job satisfaction and performance. The population in this study was 38 employees of Djatiroto Hospital, Lumajang Regency. Data was collected using a questionnaire and analyzed using structural analysis with the Smart PLS 3 statistical tool. The results showed (1) motivation positively influences job satisfaction but not significantly, 2) motivation does not influence performance, (3) culture positively and significantly influences satisfaction work, (4) culture positively influences performance but not significantly, and (5) satisfaction significantly and positively influences performance.